Functional trait variation of the endangered subshrub Noticastrum hatschbachii across contrasting coastal restinga microhabitats - Josiane Wolff-Coutinho; Makeli Garibotti Lusa; Beatriz Fernandes Torres; Ana Claudia Rodrigues; Fernanda Maria Cordeiro Oliveira; Paulo Emílio Lovato; Leonardo Khaoê Giovanetti; Daniela Ciccarelli (Flora, 2026)

Wild Arachis bradyrhizobia from distinct sites in the Brazilian Drylands: biodiversity and symbiosis with peanut (Arachis hypogaea, Fabaceae) crop - Jonnathan Whiny Moraes dos Santos; Jéssica Fernanda da Silva; Samara Lima Brito; Tancredo Augusto Feitosa de Souza; Paula Rose de Almeida Ribeiro; Ana Dolores Santiago de Freitas; Carolina Etienne de Rosália e Silva Santos; Viviane Siqueira Lima Silva; Carolina Vianna Morgante; Liziane Maria de Lima; Paulo Ivan Fernandes-Júnior (Plant Biosystems, 2026)

Land-use impacts on a soil ecosystem services index in the Brazilian Atlantic Forest biome - Maria Cecília Vieira Totti; Sérgio Henrique Godinho Silva; Bruno Montoani Silva; Ricardo de Oliveira Bordonal; Fernanda Almeida Bócoli; Vanêssa Lopes de Faria; Adriana Marcela Silva-Olaya; Andrés Olaya Montes; Alexandre Uezu; Laury Cullen Junior; Vinícius Ferreira Fernandes; Junior Cesar Avanzi (Geoderma Regional, 2026)

Benefits of Lactic Acid Bacteria Folate Synthesis in Foods and Risks Associated with Deficiency - a Review - Maria Fernanda Fernandes Siqueira; Khadija Bezerra Massaut; Patrícia Bohmer Radatz; Silvana de Souza Sigali; Igor Henrique de Lima Costa; Pedro Fernandes Viana; Graciela Volz Lopes; Wladimir Padilha da Silva; Ângela Maria Fiorentini (Probiotics and Antimicrobial Proteins, 2026)

Evaluation of overflow density flotation for microplastic assessment in highly impacted coastal zones: A methodological case study of Sepetiba Bay, Brazil - Fernanda Souza Oliveira; Tiago Vieira Fernandes; João Lucas Carvalho de Almeida; Marianna de Oliveira da Costa Maia Pinto; Everton Rangel Bispo; Maximilian Sabino Ribeiro; Danieli Martins do Carmo; Antonio Renato Bigansolli; Antonieta Middea; Edla Maria Bezerra Lima; Renata Nunes Oliveira (Regional Studies in Marine Science, 2026)

Molecular detection of pathogenic Leptospira spp. in mares with reproductive disorders enrolled in embryo transfer programs - Gustavo de Oliveira Alves Pinto; Eduarda Faria Raymundo; Gabriela Gonçalves da Silva; André de Souza Santos; Dhebora Silvério Correia; Gabriela Reis Xavier; Erika Fernanda Torres Samico-Fernandes; Gustavo Ferrer Carneiro; Maria Isabel Nogueira Di Azevedo; Rinaldo Aparecido Mota (Journal of Equine Veterinary Science, 2026)

Hormonal ratios as reliable biomarkers for sex identification in the Neotropical catfish Pimelodus maculatus - Jackellynne Fernanda Farias Fernandes; Ingrith Aparecida Mazuhy Santarosa; José Antônio de Oliveira Junior; Marisa Pereira de Sousa; Domickson Silva Costa; Maria Alcina Martins de Castro; Alex Pires de Oliveira Nuñer (Animal Reproduction Science, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Forest restoration enhances soil health in tropical agricultural landscapes assessed by soil management assessment framework (SMAF) across land uses and soil types - Vanêssa Lopes Faria; Helen Carla Santana Amorim; Maria Cecília Vieira Totti; Fernanda Almeida Bócoli; Junior Cesar Avanzi; Sérgio Henrique Godinho Silva; Alexandre Uezu; Amanda J. Ashworth; Gerson L. Drescher; Lara Mota Corinto; Samara Martins Barbosa; Vinícius Ferreira Fernandes; et al. (Geoderma Regional, 2026)

miRNA-mRNA integrative profiling in canine tubulopapillary mammary carcinoma - Nayra Cristina Herreira do Valle; Matheus Fujimura Soares; Natália Francisco Scaramele; Amanda de Oliveira Furlan; Maria Fernanda da Silva Lopes; Juliana de Souza Felix; Fernando Vissani Fernandes; Vinicius Aquiles Gomes Zamboni; Igor Luiz Salardani Senhorello; Alexandre Lima de Andrade; Flavia Lombardi Lopes (Research in Veterinary Science, 2026)

First report of Alternaria alternata causing soft rot in pitaya (Hylocereus polyrhizus) fruits in Rio Grande do Sul, Brazil - Igor Henrique de Lima Costa; Gloria Emperatriz Suqui Carchi; Isabela Schneid Kroning; Maria Fernanda Fernandes Siqueira; Frederico Schmitt Kremer; Wladimir Padilha da Silva; Cândida Renata Jacobsen de Farias; Alvaro Renato Guerra Dias (Crop Protection, 2026)

Compounded oral doxycycline in late-term pregnant mares: pharmacokinetics, fetoplacental diffusion, and neonatal safety - Fernanda T.D'el Rey Dantas; Igor F. Canisso; Lorena S. Feijó; Paula Maria Fernandes de Vasconcelos; Michel L. Campos; Alexander V. Ulanov; Zhong Li; Gino L.B.L. Pizzi; Carlos E.W. Nogueira; Bruna R. Curcio (Theriogenology, 2026)

Spatiotemporal assessment of wildfire smoke exposure using a low-cost air quality monitoring system in a developing Amazonian city - Domingas de Oliveira Almeida; Ana Carla dos Santos Gomes; Sarah Suely Alves Batalha; Tiago Bentes Mandú; Fernanda Souza do Nascimento; Glauce Vitor da Silva; Maria João Costa; Ediclê de Souza Fernandes Duarte (Journal of Environmental Management, 2026)

Trypsin inhibitor isolated from the seeds of Inga laurina (sw.) Willd decreased inflammatory and nociceptive responses in mice - Iluska Senna Bonfá; Dalila dos Santos Lencina; Jéssica de Araújo Isaías Muller; Paloma Kênia de Moraes Berenguel Lossavaro; Mila Marluce Lima Fernandes; Joyce dos Santos Lencina; Gabriel Silvino de Oliveira Venâncio; Kamylla Fernanda Souza de Souza; Julia Lopes Ribeiro Fredo; Maria Inês Lenz Souza; Saulo Euclides Silva Filho; Edgar Julian Paredes Gamero; et al. (Inflammopharmacology, 2025)

Antimicrobial resistance and biofilm production by Staphylococcus spp. and Mammaliicoccus sciuri in Inia araguaiaensis: surveillance under a one health perspective in the Amazon - Denny Parente de Sá Barreto Maia Leite; Pollyanne Raysa Fernandes de Oliveira; Flavia Cristina Matos Oliveira; Gabriel Melo-Santos; Guilherme Maricato; Karolina Rosa Fernandes Beraldo; Angélica Lúcia Figueiredo Rodrigues; Alexsandro Antonio Portilho Damasceno; Rodrigo Hipólito Tardin Oliveira; Thais Fernanda Campos Fraga-Silva; Maria Aparecida Juliano; Frederico Ozanan Barros Monteiro; et al. (Veterinary Research Communications, 2025)

Compensatory growth and physiological responses of matrinxã (Brycon amazonicus) under cyclic feed restriction - Márcia Simões dos Santos; Ariany Rabello da Silva Liebl; Ellan Rodrigo Monteiro Paes Fernandes; Christiane Patricia Feitosa de Oliveira; João Paulo Ferreira Rufino; Maria Fernanda Silva Gomes; Rayana Melo Paixão; Aline da Cunha Ferreira; Fernanda Victoria Nery Dias; Adriano Teixeira de Oliveira (Aquaculture International, 2025)

Metabolic brain changes in post-acute COVID-19: systematic review and meta-analysis of [18F]-FDG-PET findings - Izabella Fernanda Bastos Siqueira; Lais Almeida Figueiredo; Camila Emanuele Moreira Fernandes; Leandro Pinheiro Cintra; Glauber Fernandes de Oliveira; Maria Angélica Rios; Ricardo Maciel; Rodrigo Ferretjans; Nathalia Sernizon Guimarães; Luiz Alexandre Viana Magno (Brain Structure and Function, 2025)

A multispecies microcosm to assess the effect of footwear wastes on soil biota: a contribution towards sustainability - Beatriz Fernandes; Verónica Nogueira; Sirine Bouguerra; Cristiano Soares; Fernanda Fidalgo; Joana Machado; Susana M. P. Carvalho; Maria José Ferreira; Vera Pinto; José Rodrigues; Carlos M. Pereira; Ruth Pereira (Environmental Science and Pollution Research, 2025)
Due to the high quantities of solid waste with high concentrations of chromium that the footwear industry produces and its disposal sites, it is vital to understand whether leather residue itself is harmful to the ecosystem. Thus, a microcosm test with multispecies ( Brassica oleracea and Eisenia fetida ) was carried out using an agricultural soil contaminated with two different leather residues (Wet Blue and Finished Leather) from the footwear industry. After the stabilization period, Brassica oleracea seedlings and Eisenia fetida adults were exposed to these treatments. At the end of the experiment, a series of parameters were analysed in the B. oleracea leaves (leaf chlorophyl content, gas exchange measurements and photosynthetic parameters), in the E. fetida organisms (alkaline comet assay and biomarkers such as acetylcholinesterase and lipid peroxidation) and in the soils (total chromium content, enzymes activity and nitrogen mineralization and potential nitrification). In the case of soil’s enzymatic activity, even though some were significantly altered, no negative effects could be attributed to the leather residues. Moreover, the addition of residues to the soil did not significantly affect the plant species; however, the same was not observed for the earthworm E. fetida when in contact with Finished Leather. Overall, Finished Leather residue was the one that caused more effects on the parameters analysed and therefore its disposal should be carefully examined.

Artificial dyes: Health risks, environmental concerns, and the rise of natural alternatives - Fernanda Thaís Vieira Rubio; Giselle Maria Maciel; Débora Gonçalves Bortolini; Isabela de Andrade Arruda Fernandes; Alessandra Cristina Pedro; Isabela Sampaio Ribeiro; Carmen Sílvia Fávaro-Trindade; Rosane Marina Peralta; Charles Windson Isidoro Haminiuk (Trends in Food Science & Technology, 2025)

Development and characterization of active cellulose acetate films with antifungal properties of Thymus vulgaris essential oil for cheese applications - Maria Fernanda Fernandes Siqueira; Khadija Bezerra Massaut; Patrícia Radatz Thiel; Juliani Buchveitz Pires; Elessandra da Rosa Zavareze; Eliezer Avila Gandra; Wladimir Padilha da Silva; Ângela Maria Fiorentini (Brazilian Journal of Microbiology, 2025)

Gold nanorods non-functionalised and associated with gallic acid exhibit activity against non- albicans Candida species - Paulo Henrique Fonseca Carmo; Maria Fernanda Siqueira Fernandes da Costa; Anna Carolina Pinheiro Lage; Maíra Terra Garcia; Juliana Campos Junqueira (Biofouling, 2025)

Organic carbon stocks across various land use systems in Sandy Ultisols and Oxisols in Brazil - Maria Cecília Vieira Totti; Yuri Lopes Zinn; Sérgio Henrique Godinho Silva; Bruno Montoani Silva; Fernanda Almeida Bócoli; Vanêssa Lopes de Faria; Andrés Olaya Montes; Salvador Francisco Acuña-Guzman; Alexandre Uezu; Laury Cullen Junior; Vinícius Ferreira Fernandes; Junior Cesar Avanzi (Geoderma Regional, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

Drivers for agroecological transition: An analysis of 40 years of experience in Minas Gerais, Brazil - Fernanda Testa Monteiro; Alexandria Jeanne Wilson; Heitor Mancini Teixeira; Lucas Carvalho Gomes; Raphael Bragança Alves Fernandes; Maria Izabel Vieira Botelho; Ivonete Lopes; Felipe N.B. Simas; Thomas W. Kuyper; Irene Maria Cardoso (Agricultural Systems, 2025)

The influence of lactation on insulin and glucose metabolism, lipid profile, and cytokines in pregnant mares - Fernanda Jordão Affonso; Maria Augusta Alonso; Beatriz Bringel; Robert Douglas; Guilherme de Paula Nogueira; Yatta Linhares Boakari; Claudia Barbosa Fernandes (Theriogenology, 2024)

Polysaccharide fractions extracted from Lactarius quieticolor mushroom exhibit immune stimulatory activities on macrophages - Matheus Zavadinack; Daniel de Lima Bellan; Maria Paula Fernandes Bonaldi; Shayane da Silva Milhorini; Lucimara M.C. Cordeiro; Fernanda Fogagnoli Simas; Marcello Iacomini (Food Research International, 2024)

Occurrence of aflatoxins in organic rice produced and commercialized in Brazil - Natalia Aparecida Barbosa; Andrezza Maria Fernandes; Leonardo de Oliveira Seno; Maria Fernanda de Castro Burbarelli; Alessandra Lopes de Oliveira; Fernanda Bovo (Food Control, 2024)

Comparative transcriptional analysis between susceptible and resistant populations of Aedes (Stegomyia) aegypti (Linnaeus, 1762) after malathion exposure - Rogério Fernandes de Souza; Tafarel Ribeiro Amaro; Angela Maria Palacio-Cortés; Mário Antônio Navarro da Silva; Jaqueline Fernanda Dionisio; Larissa Forim Pezenti; Thayná Bisson Ferraz Lopes; Mário Sérgio Mantovani; João Antônio Cyrino Zequi; Renata da Rosa (Molecular Genetics and Genomics, 2024)

Safflower cake as an ingredient for a composite flour development towards a circular economy: extrusion versus conventional mixing - Carolina A. Antunes Amadeu; Ana Carolina Conti; Carlos Augusto Fernandes Oliveira; Silvia Maria Martelli; Fernanda Maria Vanin (Food Research International, 2024)

Liquid-liquid and solid-liquid extractions with low-temperature partitioning – A review - Adilson Correia Goulart; Alessandra Aparecida Zinato Rodrigues; Fernanda Fernandes Heleno; Anizio Marcio de Faria; Simone Machado Goulart; Maria Eliana Lopes Ribeiro de Queiroz (Analytica Chimica Acta, 2024)

Production and characterization of the lipopeptide with anti-adhesion for oral biofilm on the surface of titanium for dental implants - Fernanda Souza Carvalho; Vinícius Souza Tarabal; Diego Fernandes Livio; Luísa F. Cruz; Ana P.F. Monteiro; Adriano Guimarães Parreira; Pedro P.G. Guimarães; Karina Scheuerman; Rafael Cesar Russo Chagas; José Antônio da Silva; Daniel Bonoto Gonçalves; José Mauro Granjeiro; et al. (Archives of Microbiology, 2024)

Filamentous fungi associated with the brown mussel, Perna perna (Bivalvia: Mytilidae), off the coast of Rio de Janeiro, Brazil - Amanda Gleyce Lima de Oliveira; Renata Buarque Fernandes; Fernanda da Silva Santos; Ingrid dos Santos da Silva; Mário Jorge de Araujo Gatti; Aurea Maria Lage de Moraes; Clélia Christina Mello-Silva; Cláudia Portes Santos (Marine Biology Research, 2024)

Preventive and therapeutic vascular photobiomodulation decreases the inflammatory markers and enhances the muscle repair process in an animal model - Tainá Caroline dos Santos Malavazzi; Lucas Andreo; Andreia Martinelli; Maria Fernanda Setúbal Destro Rodrigues; Anna Carolina Ratto Tempestini Horliana; Sandra Kalil Bussadori; Kristianne Porta Santos Fernandes; Fabio Daumas Nunes; Raquel Agnelli Mesquita-Ferrari (Journal of Photochemistry and Photobiology B: Biology, 2024)

Effects of medium voltage electrical stimulation on initial pH decline and quality parameters during ageing and frozen storage of Nellore beef - Eloise Soares de Alvarenga; Maria Fernanda Isac; Alessandra Fernandes Rosa; Saulo Luz Silva; Renata Tieko Nassu; Andrea Carla da Silva Barretto (Meat Science, 2024)

Lactobacillus delbrueckii CIDCA 133 fermented milk modulates inflammation and gut microbiota to alleviate acute colitis - Luís Cláudio Lima de Jesus; Andria dos Santos Freitas; Joyce da Cruz Ferraz Dutra; Gabriela Munis Campos; Monique Ferrary Américo; Juliana Guimarães Laguna; Evandro Gonçalves Dornelas; Rodrigo Dias de Oliveira Carvalho; Kátia Duarte Vital; Simone Odília Antunes Fernandes; Valbert Nascimento Cardoso; Jamil Silvano de Oliveira; et al. (Food Research International, 2024)

Characterization of a symbiotic beverage based on water-soluble soybean extract fermented by Lactiplantibacillus plantarum ATCC 8014 - Fernanda Weber Bordini; Júlia Cristina Fernandes; Viviane Lívia Carvalho de Souza; Elaine Cristina Galhardo; Ismael Maciel de Mancilha; Maria das Graças de Almeida Felipe (Brazilian Journal of Microbiology, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Lactococcus lactis as an Interleukin Delivery System for Prophylaxis and Treatment of Inflammatory and Autoimmune Diseases - Gabriela Munis Campos; Monique Ferrary Américo; Andria dos Santos Freitas; Fernanda Alvarenga Lima Barroso; Joyce da Cruz Ferraz Dutra; Ludmila Silva Quaresma; Bárbara Fernandes Cordeiro; Juliana Guimarães Laguna; Luís Cláudio Lima de Jesus; Aparecida Maria Fontes; Alexander Birbrair; Tulio Marcos Santos; et al. (Probiotics and Antimicrobial Proteins, 2024)

Effects of amber LED on inflammatory and regulatory monocytes and lymphocytes - Kaline de Brito Sousa; Tainá Caroline dos Santos Malavazzi; Maria Fernanda Setúbal Destro Rodrigues; Tamiris Silva; Lucas Andreo; Alessandro Melo Deana; Fabio Daumas Nunes; Sandra Kalil Bussadori; Raquel Agnelli Mesquita-Ferrari; Kristianne Porta Santos Fernandes (Journal of Photochemistry and Photobiology B: Biology, 2024)

Sustainable innovations in edible films and coatings: An overview - Isabela Sampaio Ribeiro; Giselle Maria Maciel; Débora Gonçalves Bortolini; Isabela de Andrade Arruda Fernandes; Wédisley Volpato Maroldi; Alessandra Cristina Pedro; Fernanda Thaís Vieira Rubio; Charles Windson Isidoro Haminiuk (Trends in Food Science & Technology, 2024)

Assessment of quality and safety aspects of homemade and commercial baby foods - Juliana Sarmiento-Santos; Leticia Arca da Silva; Carla A. Monaco Lourenço; Roice Eliana Rosim; Carlos Augusto Fernandes de Oliveira; Sérgio Henrique Monteiro; Fernanda Maria Vanin (Food Research International, 2023)

In situ extraction/encapsulation of olive leaves antioxidants in zein for improved oxidative stability of edible oils - Amarilis Santos de Carvalho; Anielle de Oliveira; Thaysa Fernandes Moya Moreira; Luis Gustavo Médice Arabel Costa; Gabrielle Donato Marcatto; Andre da Silva Castilhos de Melo; Odinei Hess Gonçalves; Maria Inês Dias; Ricardo C. Calhelha; Lillian Barros; Patricia Valderrama; Lucio Cardozo Filho; et al. (Food Research International, 2023)

CPW partially attenuates DSS-induced ulcerative colitis in mice - Natalia Mulinari Turin de Oliveira; Vanessa S. Schneider; Laryssa Regis Bueno; Lara Luisa Valerio de Mello Braga; Karien Sauruk da Silva; Liziane Cristine Malaquias da Silva; Maria Luiza Souza; Bruna Barbosa da Luz; Cleiane Dias Lima; Ruan Sousa Bastos; Maria Fernanda de Paula Werner; Elizabeth Soares Fernandes; et al. (Food Research International, 2023)

Effects of Cecropia pachystachya on inflammatory angiogenesis induced by synthetic implants in mice - Ana Paula do Nascimento Duque; Maria Fernanda Fernandes; Pedro Henrique Santos de Freitas; Puebla Cassini-Vieira; Mariane Felipetto; Luciola Silva Barcelos; Elita Scio (Biocatalysis and Agricultural Biotechnology, 2023)

Imidacloprid: Impact on Africanized Apis mellifera L. (Hymenoptera: Apidae) workers and honey contamination - Cristiane Lurdes Paloschi; Maria Hermínia Ferreira Tavares; Elizabeth Artus Berte; Kathleen Model; Karine Medina Rosa; Fagner Goes da Conceição; Fernanda Raulino Domanski; Edgar de Souza Vismara; Paula Fernandes Montanher; Rodrigo Mendes Antunes Maciel; Leticia da Silva Ribeiro; Natalia Ramos Mertz; et al. (Chemosphere, 2023)

Spray-chilling system in the initial cooling process of swine half carcasses - Alessandra Pereira dos Santos; Fabiana Ribeiro Caldara; Alexandre Rodrigo Mendes Fernandes; Maria Fernanda de Castro Burbarelli; Bruna de Souza Eberhart; Jean Kaique Valentim; Ibiara Correia de Lima Almeida Paz; Rodrigo Garófallo Garcia; Agnês Markiy Odakura (Meat Science, 2023)

The bitter side of teas: Pesticide residues and their impact on human health - Isabela de Andrade Arruda Fernandes; Giselle Maria Maciel; Débora Gonçalves Bortolini; Alessandra Cristina Pedro; Fernanda Thaís Vieira Rubio; Karina Querne de Carvalho; Charles Windson Isidoro Haminiuk (Food and Chemical Toxicology, 2023)

Rhipicephalus microplus larvae: first report in bats, Molossus rufus - Daniele da Silva; Fabiana Raquel Ratzlaff; Vanessa Osmari; Fagner D’ambroso Fernandes; Elizabete Captivo Lourenço; Katia Maria Famadas; Aline Campos; André Alberto Witt; Susi Missil Pacheco; Fernanda Silveira Flores Vogel; Sônia de Ávila Botton; Luis Antonio Sanigioni (Veterinary Research Communications, 2023)

Azospirillum brasilense and Nitrogen Fertilizer Affect the Development and Quality of Cantaloupe Melons - Eduardo Pradi Vendruscolo; Luiz Fernandes Cardoso Campos; Alexsander Seleguini; Sebastião Ferreira de Lima; Fernanda Pacheco de Almeida Prado Bortolheiro; Murilo Battistuzzi Martins; Cássio de Castro Seron; Maria Ingrid de Souza (Journal of Plant Growth Regulation, 2023)

Antagonistic activity of Lactobacillus spp. and Bifidobacterium spp. against cariogenic Streptococcus mutans in vitro and viability when added to chewing gum during storage - Michelle Barboza Nogueira; Khadija Bezerra Massaut; Helena Reissig Soares Vitola; Maria Fernanda Fernandes Siqueira; Wladimir Padilha da Silva; Ângela Maria Fiorentini (Brazilian Journal of Microbiology, 2023)

Blocking Autophagy by the Two-Pore Channels Antagonist Tetrandrine Improves Sorafenib-Induced Death of Hepatocellular Carcinoma Cells - Letícia Paulino Sperandio; Isis Valeska F. Lins; Adolfo G. Erustes; Anderson H.F.F. Leão; Fernanda Antunes; Ingrid B.M. Morais; Heron Fernandes Vieira; Laís Maria de Campos; Claudia Bincoletto; Soraya S. Smaili; Gustavo J.S. Pereira (Toxicology in Vitro, 2023)

Neuroinflammation and hypersensitivity evidenced by the acute and 28-day repeated dose toxicity tests of ostrich oil in mice - Jose Roberto Santin; Mainara Adriane Tesser Kopp; Thiago Patrício Correa; Jéssica Melato; Larissa Benvenutti; Roberta Nunes; Fernanda Capitanio Goldoni; Yasmin Beatrisse Klein Patel; Jade André de Souza; Suzany Hellen da Silva Soczek; Elizabeth Soares Fernandes; Maria Verônica Dávila Pastor; et al. (Food and Chemical Toxicology, 2023)

Influence of lactational status of the surrogate mare during early pregnancy on inflammatory markers in subsequently born foals - Fernanda Jordão Affonso; Maria Augusta Alonso; Beatriz Alves Bringuel; Robert Hazourd Douglas; Guilherme de Paula Nogueira; Claudia Barbosa Fernandes (Journal of Equine Veterinary Science, 2023)

The influence of mare's lactational status during early pregnancy on metabolism of foals up to 28 days of age - Fernanda Jordão Affonso; Maria Augusta Alonso; Beatriz Alves Bringuel; Robert Douglas; Guilherme de Paula Nogueira; Claudia Barbosa Fernandes (Journal of Equine Veterinary Science, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Quantification of SARS-CoV-2 in wastewater samples from hospitals treating COVID-19 patients during the first wave of the pandemic in Brazil - Juliana Calábria de Araújo; Camila L. Madeira; Thiago Bressani; Cíntia Leal; Deborah Leroy; Elayne C. Machado; Luyara A. Fernandes; Maria Fernanda Espinosa; Gabriel Tadeu O. Freitas; Thiago Leão; Vera Tainá Mota; Alyne Duarte Pereira; et al. (Science of The Total Environment, 2023)

Effects of dredging activities and seasonal variation on coastal plankton assemblages: results from 10 years of environmental monitoring - Lohengrin D. A. Fernandes; Guilherme N. Corte; Laura Moura; Carolina Reis; Thiago Matos; Danubia Moreno; Pedro Sant’ Anna Cortez; Wanderson Fernandes de Carvalho; Wanda Monteiro-Ribas; José Eduardo A. Gonçalves; Fernando Ribeiro; Fernanda Thomazelli; et al. (Environmental Monitoring and Assessment, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Aflatoxins in Fish Feed and Tilapia ( Oreochromis niloticus ) Tissues in Brazil - Silvia Helena Seraphin de Godoy; Amanda Larissa Gomes; Maria Fernanda de Castro Burbarelli; Carolina Maria Bedoya-Serna; Andrea Vasquez-Garcia; Milena Penteado Chaguri; Ricardo Luiz Moro de Sousa; Andrezza Maria Fernandes (Journal of Aquatic Food Product Technology, 2022)

Porcine Primordial Germ Cell-Like Cells Generated from Induced Pluripotent Stem Cells Under Different Culture Conditions - Naira Caroline Godoy Pieri; Aline Fernanda de Souza; Ramon Cesar Botigelli; Laís Vicari de Figueiredo Pessôa; Kaiana Recchia; Lucas Simões Machado; Mayra Hirakawa Glória; Raquel Vasconcelos Guimarães de Castro; Diego Feitosa Leal; Paulo Fantinato Neto; Simone Maria Massami Kitamura Martins; Daniele dos Santos Martins; et al. (Stem Cell Reviews and Reports, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Investigating the Effect of Inosine on Brain Purinergic Receptors and Neurotrophic and Neuroinflammatory Parameters in an Experimental Model of Alzheimer’s Disease - Fernanda Cardoso Teixeira; Mayara Sandrielly Pereira Soares; Eduardo Bierhaus Blödorn; William Borges Domingues; Karine Paula Reichert; Adriana Maria Zago; Fabiano Barbosa Carvalho; Jessie Martins Gutierres; Relber Aguiar Gonçales; Marilda da Cruz Fernandes; Vinicius Farias Campos; Maria Rosa Chitolina; et al. (Molecular Neurobiology, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Evaluation of the anticonvulsant and antioxidant activity of alkylated cardanol in rodents - Danielle Fernanda Fernandes Vieira; Antonio Luiz Gomes Junior; Keylla da Conceição Machado; Wcleubianne Matias Nascimento Maia; Tassio Lessa do Nascimento; Maria Alexsandra de Sousa Rios; Luciano da Silva Lopes (Natural Product Research, 2021)

Microscopic Detection, Hematological Evaluation and Molecular Characterization of Piroplasms from Naturally Infected Dogs in Rio de Janeiro, Brazil - Fernanda Barbosa dos Santos; Gilberto Salles Gazêta; Laís Lisboa Corrêa; Lucas Fernandes Lobão; João Pedro Siqueira Palmer; Laís Verdan Dib; José André Lessa Damasceno; Nicole Oliveira Moura-Martiniano; Otilio Machado Pereira Bastos; Claudia Maria Antunes Uchôa; Alynne da Silva Barbosa (Acta Parasitologica, 2021)

Anti-inflammatory and antioxidant properties of Alternanthera brasiliana improve cutaneous wound healing in rats - Rogério Marchete; Sarah Oliveira; Leonardo Bagne; Jennyffer Ione de Souza Silva; Ana Paula Valverde; Andrea Aparecida de Aro; Mariana Moreira Figueira; Marcio Fronza; Thainá Mikaela Bressam; Vivian Fernandes Furletti de Goes; Fernanda Oliveira de Gaspari de Gaspi; Gláucia Maria Tech dos Santos; et al. (Inflammopharmacology, 2021)

Potential of Bacterial Strains Isolated from Ironstone Outcrops Bromeliads to Promote Plant Growth Under Drought Conditions - Rodrigo Mattos Silva Galeano; Fernanda Maria de Russo Godoy; Laís Mayara Melo Duré; Paulo Ivan Fernandes-Júnior; José Ivo Baldani; Gecele Matos Paggi; Fabiana Fonseca Zanoelo; Marivaine Silva Brasil (Current Microbiology, 2021)

Long-term eutrophication and contamination of the central area of Sepetiba Bay (SW Brazil) - Wellen Fernanda Louzada Castelo; Maria Virgínia Alves Martins; Paulo Alves de Lima Ferreira; Rubens Figueira; Carolina Ferreira da Costa; Lauren Brito da Fonseca; Sérgio Bergamashi; Egberto Pereira; Denise Terroso; Anita Fernandes Souza Pinto; Maurício Bulhões Simon; Orangel Antonio Aguilera Socorro; et al. (Environmental Monitoring and Assessment, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Pharmacologic potential of new nitro-compounds as antimicrobial agents against nosocomial pathogens: design, synthesis, and in vitro effectiveness - Jéssica Tauany Andrade; Silmara Lucia Grego Alves; William Gustavo Lima; Carla Daiane Ferreira Sousa; Lucas Fernandes Carmo; Nívea Pereira De Sá; Fernanda Barbara Morais; Susana Johann; José Augusto Ferreira Perez Villar; Jaqueline Maria Siqueira Ferreira (Folia Microbiologica, 2020)

Lymphatic vessels in human adipose tissue - Patricia de Albuquerque Garcia Redondo; Fernanda Gubert; Camila Zaverucha-do-Valle; Tatiana Pereira Pena Dutra; Jackline de Paula Ayres-Silva; Natasha Fernandes; Antonio Augusto Peixoto de Souza; Marilena Loizidou; Christina Maeda Takiya; Maria Isabel Doria Rossi; Radovan Borojevic (Cell and Tissue Research, 2020)
Despite being considered present in most vascularised tissues, lymphatic vessels have not been properly shown in human adipose tissue (AT). Our goal in this study is to investigate an unanswered question in AT biology, regarding lymphatic network presence in tissue parenchyma. Using human subcutaneous (S-) and visceral (V-) AT samples with whole mount staining for lymphatic specific markers and three-dimensional imaging, we showed lymphatic capillaries and larger lymphatic vessels in the human VAT. Conversely, in the human SAT, microcirculatory lymphatic vascular structures were rarely detected and no initial lymphatics were found.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

An exploration of the aversive properties of 2-deoxy-D-glucose in rats - Thomas Horman; Maria Fernanda Fernandes; Yan Zhou; Benjamin Fuller; Melissa Tigert; Francesco Leri (Psychopharmacology, 2018)

Microbiological control and antibacterial action of a propolis-containing mouthwash and control of dental plaque in humans - Karina Basso Santiago; Gilce Maria Piana; Bruno José Conti; Eliza de Oliveira Cardoso; Bruna Fernanda Murbach Teles Andrade; Mirella Rossitto Zanutto; Vera Lúcia Mores Rall; Ary Fernandes; José Maurício Sforcin (Natural Product Research, 2018)

Effect of simvastatin on sensorial, motor, and morphological parameters in sciatic nerve crush induced-neuropathic pain in rats - Claudia Rita Corso; Daniel Fernandes Martins; Stephanie Carvalho Borges; Olair Carlos Beltrame; José Ederaldo Queiroz Telles; Nilza Cristina Buttow; Maria Fernanda de Paula Werner (Inflammopharmacology, 2018)

The Inventory of Geological Heritage of the State of São Paulo, Brazil: Methodological Basis, Results and Perspectives - Maria da Glória Motta Garcia; José Brilha; Flávia Fernanda de Lima; Jean Carlos Vargas; Annabel Pérez-Aguilar; Adriana Alves; Ginaldo Ademar da Cruz Campanha; Wânia Duleba; Frederico Meira Faleiros; Luiz Alberto Fernandes; Marisa de Souto Matos Fierz; Maria Judite Garcia; et al. (Geoheritage, 2018)

Deltamethrin-induced nuclear erythrocyte alteration and damage to the gills and liver of Colossoma macropomum - Fernanda dos Santos Cunha; Natalino da Costa Sousa; Rudã Fernandes Brandão Santos; Juliana Oliveira Meneses; Márcia Valéria Silva do Couto; Fabrício Tavares Cunha de Almeida; José Guedes de Sena Filho; Paulo César Falanghe Carneiro; Alexandre Nizio Maria; Rodrigo Yudi Fujimoto (Environmental Science and Pollution Research, 2018)

Tailoring Lipid and Polymeric Nanoparticles as siRNA Carriers towards the Blood-Brain Barrier – from Targeting to Safe Administration - Maria João Gomes; Carlos Fernandes; Susana Martins; Fernanda Borges; Bruno Sarmento (Journal of Neuroimmune Pharmacology, 2017)

Pathological concentrations of homocysteine increases IL-1β production in macrophages in a P2X7, NF-ĸB, and erk-dependent manner - Rafael Fernandes Zanin; Letícia Scussel Bergamin; Fernanda Bueno Morrone; Robson Coutinho-Silva; Angela Terezinha de Souza Wyse; Ana Maria Oliveira Battastini (Purinergic Signalling, 2015)

Relationship between physical and chemical soil attributes and plant species diversity in tropical mountain ecosystems from Brazil - Fernanda de Carvalho; Edward Luis Godoy; Francy J. G. Lisboa; Fatima Maria de Souza Moreira; Francisco Adriano de Souza; Ricardo Luis Louro Berbara; G. Wilson Fernandes (Journal of Mountain Science, 2014)

Phthaloyl amino acids as anti-inflammatory and immunomodulatory prototypes - Ana Cristina Lima Leite; Fábio Fernandes Barbosa; Marcos Veríssimo de Oliveira Cardoso; Diogo R. M. Moreira; Lucas Cunha D. Coêlho; Elany Barbosa da Silva; Gevanio Bezerra de Oliveira Filho; Valdênia Maria Oliveira de Souza; Valéria Rêgo A. Pereira; Luiza de C. Reis; Paulo Michel Pinheiro Ferreira; Claudia Pessoa; et al. (Medicinal Chemistry Research, 2014)

Interaction between obesity-related genes, FTO and MC4R, associated to an increase of breast cancer risk - Patrícia Amorim da Cunha; Lia Kubelka de Carlos Back; Aline Fernanda Rodrigues Sereia; Clara Kubelka; Maria Cecíia Menks Ribeiro; Bráulio Leal Fernandes; Ilíada Rainha de Souza (Molecular Biology Reports, 2013)

P2X7 receptor activation leads to increased cell death in a radiosensitive human glioma cell line - Marina Petersen Gehring; Talita Carneiro Brandão Pereira; Rafael Fernandes Zanin; Magali Carvalho Borges; Aroldo Braga Filho; Ana Maria Oliveira Battastini; Maurício Reis Bogo; Guido Lenz; Maria Martha Campos; Fernanda Bueno Morrone (Purinergic Signalling, 2012)

Ecological implications on the aggregation of Amblyomma fuscum (Acari: Ixodidae) on Thrichomys laurentius (Rodentia: Echimyidae), in northeastern Brazil - Filipe Martins Aléssio; Filipe Dantas-Torres; Daniel Barreto Siqueira; Marie-Hélène Lizée; Maria Fernanda Vianna Marvulo; Thiago Fernandes Martins; Marcelo Bahia Labruna; Jean Carlos Ramos Silva; Jean-François Mauffrey (Experimental and Applied Acarology, 2012)

HFE, MTHFR, and FGFR4 genes polymorphisms and breast cancer in Brazilian women - Anna P. Batschauer; Nathalia G. Cruz; Vanessa C. Oliveira; Fernanda F. Coelho; Izabela R. Santos; Michelle T. Alves; Ana P. Fernandes; Maria G. Carvalho; Karina B. Gomes (Molecular and Cellular Biochemistry, 2011)

Mutations in methylenetetrahydrofolate reductase and in cysthationine beta synthase: is there a link to homocysteine levels in peripheral arterial disease? - Maria E. R. C. Santos; Francisco das C. L. e Silva; Karina B. Gomes; Ana Paula M. Fernandes; Fernanda R. Freitas; Mayara C. Faria; Ana Paula L. Mota; Maria G. Carvalho (Molecular Biology Reports, 2011)

Partial 5p monosomy or trisomy in 11 patients from a family with a t(5;15)(p13.3;p12) translocation - Acácia Fernandes Lacerda de Carvalho; Fernanda Teixeira da Silva Bellucco; Leslie Domenici Kulikowski; Maria Betânia Pereira Toralles; Maria Isabel Melaragno (Human Genetics, 2008)

Hepatotoxicity of 3,4-methylenedioxyamphetamine and ?-methyldopamine in isolated rat hepatocytes: formation of glutathione conjugates - Maria Lourdes Bastos; Mrcia Carvalho; Nuno Milhazes; Fernando Remio; Fernanda Borges; Eduarda Fernandes; Francisco Amado; Terrence J. Monks; Flix Carvalho (Archives of Toxicology, 2004)

Role of metabolites in MDMA (ecstasy)-induced nephrotoxicity: an in vitro study using rat and human renal proximal tubular cells - Má rcia Carvalho; Gabrielle Hawksworth; Nuno Milhazes; Fernanda Borges; Terrence Monks; Eduarda Fernandes; Fé lix Carvalho; Maria Bastos (Archives of Toxicology, 2002)